2017
DOI: 10.1111/jfbc.12380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-fermentation saignée treatment on phenolic compound profile in wine made of Cabernet Sauvignon

Abstract: The saignée method was applied to Vitis vinifera L. Cabernet Sauvignon wine making to improve the phenolic component in fresh and 1‐year aged wines. The physicochemical properties of the saignée‐treated wine were similar to those of the control. A moderate enhancement of the total non‐anthocyanin content was observed in the saignée‐treated wine, but this was not significant (p > .05). After fermentation, the anthocyanin content was increased in the treated wine compared to the control (p ≤ .05). Anthocyanin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
(50 reference statements)
2
8
0
Order By: Relevance
“…These results suggested that the Marquette wine after using saignée treatment (e.g., 9% removed juice) has remained relatively unchanged in terms of the basic chemical properties in the finished wines. These results were consistent with a previous study in Cabernet Sauvignon, as no significant difference was observed in basic chemical properties between saignée-treated wine (14% juice run-off) and the control after one year of aging [ 24 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggested that the Marquette wine after using saignée treatment (e.g., 9% removed juice) has remained relatively unchanged in terms of the basic chemical properties in the finished wines. These results were consistent with a previous study in Cabernet Sauvignon, as no significant difference was observed in basic chemical properties between saignée-treated wine (14% juice run-off) and the control after one year of aging [ 24 ].…”
Section: Resultssupporting
confidence: 93%
“…Since most of polyphenols accumulate in the grape skins, removing the juice with certain level or ratio would theoretically increase the concentration of water-soluble compounds in the juice. Most research on Vitis vinifera red wines revealed that saignée treatment led to more red hue and higher phenolic compounds extraction in different varieties, such as Cabernet Sauvignon [ 24 , 25 ], Shiraz [ 26 , 27 ], and Monastrell [ 28 ]. Considering the correlation between the quality and the concentration of phenolics in the finished wine, more pronounced effects of the saignée treatment on color stability and phenolic compounds extraction were observed with the increase in the juice run-off percentage [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that a strong relationship existed between the must volume: solids ratio and both nonbleachable pigment and colour density, at R 2 = 0.97 and R 2 = 0.99, respectively. Many other studies have shown comparable results for saigneé treatments with up to 20% of juice runoff (Singleton 1972, Gawel et al 2001, Harbertson et al 2009,Wu et al 2017. It was highlighted, however, in a recent review (Godden 2019) that a proportional increase in measures of wine phenolics has not been consistently observed with the extent of saigneé.…”
Section: Implications Of Must Volume : Solids Ratio On Wine Phenolicsmentioning
confidence: 94%
“…Process of grapes such as dehydration, maceration, and pre‐fermentation could significantly affect the phenolic compound profiles of wines (Alencar et al., ; Panceri & Bordignon‐Luiz, ; Wu et al., ). However, some grape varieties, and therefore the wines, may be genetically richer in polyphenols than the others (Padilha, Camarão Telles Biasoto, Corrêa, dos Santos Lima, & Pereira, ; Poudel, Tamura, Kataoka, & Mochioka, ).…”
Section: Introductionmentioning
confidence: 99%